Nikah MBA (Married by Accident) dalam Tinjauan Hadits Nabawi - Ridwan Hasbi (An-Nida', 2013)
MBA Marriages is a term used to refer to the marriage ceremony performed when a woman is pregnant as a result of fornication. Marriages take place as a way to cover the sin and the applicable law should hudud. The paradigm of the hadiths of the Prophet in a very complete history of marriage MBA, both with regard to validity of a marriage ceremony, because of the sin of adultery marriage with nothing to do and the wedding solution. The basic framework of the Prophet’s hadiths state that the MBA is not a valid marriage, not the way make it as a means of closing the damage or danger that would arise from not married is contrary to the hudud ISSUES, but on the other hand the adverse effects relating to the status of marriage MBA descent children who are not RELATED to the male offspring who married his mother while pregnant out of wedlock, dropping out and not mutually inherits guardianship.